Two Point Mutations on CYP51 Combined With Induced Expression of the Target Gene Appeared to Mediate Pyrisoxazole Resistance in Botrytis cinerea - Zhang, Can; Imran, Muhammad; Liu, Min; Li, Zhiwen; Gao, Huige; Duan, Hongxia; Zhou, Shunli; Liu, Xili (Frontiers in Microbiology, 2020)
Botrytis cinerea is a destructive plant pathogenic ascomycete that causes serious pre- and post-harvest losses worldwide. The novel sterol 14α-demethylase inhibitor (DMI) pyrisoxazole was recently registered for the control of tomato gray mold caused by B. cinerea in China. Baseline sensitivity of 110 B. cinerea isolates collected from nine provinces in China to pyrisoxazole was demonstrated, with a mean EC50 of 0.057 ± 0.029 μg/ml. Eleven stable mutants resistant to pyrisoxazole were generated via UV irradiation (RU-mutants) and spontaneous selection (RS-mutants) of conidia. The eﬃcacy of pyrisoxazole against the resistant mutants was signiﬁcantly lower than that of the sensitive isolates. Most of the pyrisoxazole- resistant mutants were less fit than the sensitive isolates, with reduced sporulation, conidia germination, sclerotium production, and pathogenicity, which was confirmed by the competitive ability test. Positive cross-resistance was only observed between pyrisoxazole and the DMIs tebuconazole and prochloraz, but not between pyrisoxazole and non-DMIs iprodione, procymidone, diethofencarb, fluazinam, pyrimethanil, or fludioxonil. A two-point mutation, at G476S and K104E in the RU-mutants, and a one point mutation, M231T, in the RS-mutants, were detected in the CYP51 protein of the resistant mutants. When exposed to pyrisoxazole, the induced expression level of CYP51 increased in the resistant isolates as compared to sensitive ones. Molecular docking suggested that G476S and M231T mutations both led to the loss of electrostatic interactions between CYP51 and pyrisoxazole, while no change was found with the K104E mutation. Thus, two point mutations on CYP51 protein combined with induced expression of its target gene appeared to mediate the pyrisoxazole resistance of B cinerea.